1996
DOI: 10.1007/bf02353672
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of six deconvolution techniques

Abstract: We present results for the comparison of six deconvolution techniques. The methods we consider are based on Fourier transforms, system identification, constrained optimization, the use of cubic spline basis functions, maximum entropy, and a genetic algorithm. We compare the performance of these techniques by applying them to simulated noisy data, in order to extract an input function when the unit impulse response is known. The simulated data are generated by convolving the known impulse response with each of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 17 publications
1
51
0
1
Order By: Relevance
“…Regularization is another possibility to "force" the inverse filtered object function to have some prescribed properties. 33,34 It is worth mentioning a comparative study of six different deconvolution techniques by Madden et al, 35 where the reader can find a numerical analysis of some specific methods used to deconvolve pharmacokinetic drug response functions. However, these methods apply either an implicit model function (e.g., cubic splines) or an interpolation of the original experimental data to a substantially increased grid size compared to the number of measured points.…”
Section: Deconvolution Methodsmentioning
confidence: 99%
“…Regularization is another possibility to "force" the inverse filtered object function to have some prescribed properties. 33,34 It is worth mentioning a comparative study of six different deconvolution techniques by Madden et al, 35 where the reader can find a numerical analysis of some specific methods used to deconvolve pharmacokinetic drug response functions. However, these methods apply either an implicit model function (e.g., cubic splines) or an interpolation of the original experimental data to a substantially increased grid size compared to the number of measured points.…”
Section: Deconvolution Methodsmentioning
confidence: 99%
“…Madden et al (1996) undertook a comparison of six possible deconvolution techniques for solving Equation 13. Of the six approaches, they concluded that the best in terms of overall performance was 'maximum entropy deconvolution', developed by Skilling and Bryan (1982).…”
Section: Deconvolutionmentioning
confidence: 99%
“…Compared to all these previous techniques, the entropy maximizations algorithm [14,15] performs better in reducing the RMS error on the solution [16].…”
Section: Introductionmentioning
confidence: 97%